Factors Affecting Treatment Adherence Among Patients with Tuberculosis in Indonesia: Literature Review - Fahrul Islam; Haeranah Ahmad; Nurbaya; Masnaeni Ahmad; Ansar; Kadar Ramadhan; Muhammad Syukri; Syafran Arrazy; Agung Aji Perdana; Deborah Siregar; Nining Ade Ningsih; Ikes Dwi Astuti; St. Kadijah Hamid; Asrul Hamonangan Pasaribu (Journal of Public Health and Pharmacy, 2024)
Introduction: Tuberculosis (TB) is the leading cause of death from infectious diseases in the world and Indonesia is the second largest contributor to TB cases after India. Treatment adherence problems are a major obstacle to TB elimination. The purpose of this Literature Review is to determine the factors that affect treatment adherence among TB patients in Indonesia. Methods: Literature obtained from Science Direct, PubMed, and Google Scholar; published from 2018 – 2023, research from reputable international journals and from national journals at least with SINTA 3, located in Indonesia. Indonesian and English with full text of all types of research designs. Article selection was carried out using the method "Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) and analyzed using descriptive analysis techniques. Results: A total of 225 articels were deemed appropriate for the topic, but only 15 articles were included based on inclusion criteria. It was found that there are several factors that affect treatment adherence in tuberculosis patients in Indonesia, namely: predisposing factors as many as 11 articles (age, education, occupation, knowledge, self-efficacy, concordance, health behavior, motivation, marital status, income level, drug side effects, already feeling cured, and duration of treatment). Reinforcing factors as many as 2 articles (family support). Enabling factors as many as 5 articles (the role of officers, reminder SMS messages from officers, health counseling, and distance of residence to health services). Conclusion: The most dominant factor affecting treatment adherence among tuberculosis patients in Indonesia is the Predesposising factors, namely education and sefl-efficacy.